Surface properties of lactobacilli isolated from healthy subjects - Colloca, M. E. (2008)
OBJECTIVE: Lactobacilli are considered cariogenic micro-organismS. As oral species of lactobacilli have not been thoroughly described, the aim of this work was to isolate and identify these organisms from teeth, tongue, saliva and gum of healthy patients and to describe some of their surface properties. SUBJECTS: Forty-four subjects from Tucumán, Argentina, with D, d and M, m indices equal to 0. MATERIALS AND METHODS: Samples were obtained from different areas of the oral cavity. Microorganisms were cultured in lactobacilli selected media (LBS) and identified morphologically and biochemically. Hydrophobicity was analysed by partition in organic solvents, acidity by affinity with chloroform and basicity with ethyl acetate (MATH method), aggregation and coaggregation in presence of (NH4)2SO4, and haemagglutination with ABO erythrocytes in microplates. RESULTS: Eighty-five lactobacilli were isolated; 29.4% were homofermenter, 44.7% facultative heterofermenter and 25.9% obligate heterofermenter. Predominant species were L.fermentum, L.plantarum, L.salivarius, and L.rhamnosus. Most of the strains showed moderate to high hydrophobicity and demonstrated high acid and basic surface charges with almost 40% showing salt aggregation. Few strains haemagglutinated. CONCLUSIONS: A variety of Lactobacillus species were isolated from healthy mouths, some of whom showed adhesion-related properties such as high hydrophobicity and charged surfaceS. Probable mechanisms related to the ecological behaviour of lactobacilli in the oral cavity are discussed.